Impact of Microfinance on Small Business Growth and Economic Development in Low-Income Communities - Karna, Poonam Kumari Labh (Mikailalsys Journal of Advanced Engineering International, 2025)
Microfinance provides small loans, savings accounts, and financial education to low-income communities. It promotes entrepreneurship, small business growth, and economic development. Its efficacy is disputed, with regional results varying. Microfinance's benefits, drawbacks, and future possibilities for small enterprises are examined in this article. Microfinance empowers women by expanding financial independence and employment engagement beyond economic inclusion. Microfinance Institutions (MFIs) provide lending, savings, and insurance to low- to moderate-income individuals and small companies, according to the World Bank. Micro-loans help entrepreneurs grow, create jobs, and stabilize finances in underdeveloped economies. Through diverse funding strategies, MFIs promote SMEs, advancing economic and social advancement. By enhancing education, healthcare, and economic self-sufficiency, microfinance improves long-term financial security. However, high capital costs and interest rates remain issues. Borrowers have financial limits because many MFIs are funded by commercial banks. This research examines microfinance's role in poverty reduction, obstacles, and its potential to create sustainable economic growth. Understanding its successes and weaknesses is crucial to enhancing its effectiveness and maintaining long-term financial inclusion in low-income communities.